Empowering students’ numeracy skills: Mathematics teachers’ perceptions regarding the effectiveness and challenges of Indonesian national curriculum and the programs – A mixed method study - Hidayah, Irma Rachmah; Sa'dijah, Cholis; Anwar, Lathiful; Yerizon, Yerizon; Arnawa, I Made (IKIP Siliwangi and I-MES, 2025)
As the Indonesian National Curriculum (INC), the Merdeka curriculum was implemented in response to students' difficulties in comprehending and utilizing basic mathematics, contributing to low numeracy skills. This study investigated mathematics teachers' perceptions in Indonesia concerning the effectiveness of INC and the supporting programs, such as the National Assessment (NA) and Pancasila Student Profile (PSP), in improving students' numeracy skills. It also aimed to identify mathematics teachers' challenges in integrating numeracy skills into the curriculum and these programs. A mixed-method study with a sequential explanatory design was used to achieve this objective. The data collection was carried out through quantitative and qualitative approaches. Closed questionnaires were explicitly used for quantitative data, while open questionnaires and interviews were used for qualitative data. Inferential statistics were used to analyze the quantitative data and a thematic analysis for qualitative data. The quantitative results showed that most teachers positively perceived the effectiveness of INC and the programs in empowering students' numeracy skills. The implementation of INC and PSP significantly influenced the empowerment of numeracy skills. The qualitative analysis provided an in-depth exploration of teachers' perceptions and the challenges faced in promoting numeracy skills in implementing INC and the programs.